AYURVEDIC MANAGEMENT OF DUCHENNE MUSCULAR DYSTROPHY: A SHORT REVIEW - Patankar, Akshay A; Rathi, Renu B (International Journal of Research -GRANTHAALAYAH, 2019)
Duchenne muscular dystrophy is a neuromuscular disorder characterized by deficient dystrophin protein in the muscle. The main symptoms the patient presented were delay in expressive and receptive language development, visual discontent, hyperkinetic behaviour, and inability to initiate and maintain social contact with peers. The data obtained from the family, following clinical examination, laboratory investigation results and assessment of mental status were significant for the diagnosis of Autism Spectrum Disorder, hyperkinetic behaviour and Duchenne Muscular Dystrophy. In Ayurveda it has been classified under Medomamsa dusti further vitiates the Vata doshas occurs due to the Bheejabagahaavyava Dusti. In modern medicine there is no significant treatment available for this diseases while in Ayurvedic panchakrma therapy shows significant results in all signs and symptoms of this diseases.